A Comparison of Spatial Pattern Detection Methods for Major Cancer Mortality in Korea. (September 2016) - Kim, Jiyu; Lee, Myeonggyun; Jung, Inkyung
Spatial pattern detection can be a useful tool for understanding the geographical distribution of cancer mortality. This study compared the results from several special analysis methods to examine the geographical variations in Korean major cancer mortality during 2010 to 2013. The spatial scan statistic and Tango's method were used to detect spatial clusters with unusually high or low rates. The local indicator of spatial association was used for cluster detection with accounting for spatial autocorrelation among adjacent areas. A nonparametric approach was used to identify local districts with significantly higher or lower rates, compared to the average national rate. The different methods revealed similar results in the overall patterns, but slightly different specific results. These techniques can provide complementary information and should be used based on the distinguishing features of each method. It may be better to use several different methods for these analyses rather than a single method.